Walkway Subgrade Stabilization Using Fly Ash - Leenaloshni, Joganathan; A., Zulkiple (2013)
The effectiveness of fly ash use in the stabilization of soil and the method that is used to test the strength of the subgrade soil with different amount of fly ash in order to stabilize the soil were studied. In this research project, the by-product of coal which is the fly ash was used as the subgrade stabilization material for walkway. The primary reason fly ash is used in soil stabilization applications is to improve the compressive and shearing strength of soils. The soil effectiveness was tested by using different percentages of fly ash which is 5%, 10% and 15%.Laboratory tests such as the moisture content, particle size analysis, liquid limit, plastic limit,standard proctor and California Bearing Ratio (CBR) were carried out for the soil sample in order to study the engineering properties of the soil and to determine the optimum moisture content of fly ash that give maximum CBR value for 5%, 10% and 15% soil-fly ash mixture. If the CBR value is increasing by adding the fly ash to the soil there is effectiveness in increasing the soil strength and vice versa.